Oligostilbenoids with Acetylcholinesterase Inhibitory Activity from Dipterocarpus alatus - Chen, Chao Jun; Jiang, Rong; Wang, Gang; Jiao, Rui Hua; Tancharoen, Chompoonuch; Sudto, Kanokorn; Vajarothai, Sranya; Hannongbua, Supa; Ge, Hui Ming; Tan, Ren Xiang (Planta Medica, 2014)
Phytochemical investigation of the stem wood of Dipterocarpus alatus led to the isolation and characterization of four new oligostilbenoids, dipterocarpols A–D (1–4), together with two known resveratrol oligomers, hopeahainol (5) and hopeafuran (6). The structures of the new compounds were determined by comprehensive spectral analysis including 1D and 2D NMR, and high-resolution MS. The absolute configurations were determined by NOESY and CD spectra. Dipterocarpol A (1) and hopeahainol A (5) showed moderate acetylcholinesterase inhibitory activity with IC50 values of 8.28 µM and 11.28 µM, respectively. Furthermore, the discovery of compound 3 gave the first evidence that the biosynthetic origin of resveratrol aneuploids is related to the loss of a half resveratrol unit by oxidative cleavage.
Keywords: Dipterocarpus alatus; Dipterocarpaceae; oligostilbenoids; acetylcholinesterase inhibitory activity